Pengendalian Hama Tanaman Cabai Rawit Dan Dampaknya Terhadap Pendapatan Petani Di Desa Lalopisi Kecamatan Meluhu - Milawati Saranani (Jurnal Riset Rumpun Ilmu Tanaman, 2023)
This research aims to determine the control of thrips pests on the production of cayenne pepper plants and the impact of controlling thrips pests on farmers' income in Lalopisi Village, Meluhu District, Konawe Regency. The location of this research is Lalopisi Village, Meluhu District, Konawe Regency. The number of samples in this research was 10 farmers. To complete the first and second research objectives, namely by using a qualitative descriptive method, based on the research results, it shows that thrips pest control on cayenne pepper plants in Lalopisi Village, Meluhu District, Konawe Regency is carried out in two ways, namely mechanical pest control and chemical pest control. . Control of thrips sp pest attacks. carried out by respondents or cayenne pepper farmers in Lalopisi Village, Meluhu District, Konawe Regency, had an impact on increasing the production and income of cayenne pepper farming.